The Impact of Motivation on Employees' Job Satisfaction. Motivation and Job Satisfaction - Bagajjo, Wosenyeleh Semeon (Technium Social Sciences Journal, 2021)
This study in the title’ Impact of Motivation on Employees Job Satisfaction’ was conducted in Hawassa College of Health Science, one of government health science colleges in southern Ethiopia. The specific objectives of the study were analyzing the need for motivation, different motivational methods found in the college, methods used to retain employees in the college, and investigating the importance of job satisfaction achieved through motivation. To achieve the objectives set, primary and secondary sources data were used. Primary data was collected both from managerial and non-managerial employees of the college. The total population of the College is 230 from which 120 samples was taken using Convenience sampling technique. Much of the data was collected from the academic category since this category performs the core jobs of the college which is teaching-learning process. Data collected was analyzed using MS Excel, and under each statistical figure important interpretations were made. Data was analyzed in the order of objectives set. The findings of the research revealed that motivation is needed for creating job satisfaction, reducing employees turnover, retaining employees in the college, letting employees concentrate on goals, boosting employees productivity, accepting organizational change, increasing willingness to contribute, creating cooperation among the employees of the college, and building good image to the college. The research also found that the college’s motivational methods are training, high basic salary, career path, communication, autonomy, exposure, social gatherings, and additional responsibility. These methods are also capable of retaining employees in the college. Job satisfaction is important for retaining employees in the college, increasing employee morale, efficient resource utilization, better performance, good time management, innovation, and realizing college’s vision. Also, the finding of the research revealed that achievement, growth or possibility of growth, the work itself, recognition, responsibility, and advancement were mentioned as factors of motivation. On the other hand, supervision-technical, personal life, job security, working condition, college’s policy and administration, salary and status were mentioned as factors causing dissatisfaction. On the basis of above mentioned findings, the study suggested some recommendations that are the college should keep on knowing the need for motivation, other dominant motivational methods should be created, hygiene factors should carefully be managed, the college should conduct exit interview.